Evaluating the risk of malnutrition in the group of patients being prepared for surgery - Łuczyk, Marta; Długoborska, Klaudia; Łuczyk, Robert; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2017)
Introduction. Malnutrition is defined as an eating disorder or a nutritional state in which micro- and macronutrient deficiencies, as well as caloric deficiency, have a negative effect on the human body, its tissues and the well-being of the organism and the results of treatment [3]. Aim of the job. Assess the risk of malnutrition in patients being prepared for surgery. Results. When assessing the risk of malnutrition using the NRS 2002 Scaleit was found that 89,93% (n = 92) patients required careful observation and repeated nutrition assessment in 7 days, while in 10,68% (n = 11) it was necessary to introduce nutritional treatment before surgery. Conclusions. <p class="MsoListParagraphCxSpFirst" style="margin-top: 0cm; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 18.0pt; mso-add-space: auto; text-align: justify; text-justify: inter-ideograph; text-indent: -18.0pt; line-height: 150%; mso-list: l0 level1 lfo1;"><!--[if !supportLists]-->1. <!--[endif]-->Most of them had normal nutrition and if they were malnourished, it was mostly mild. <p class="MsoListParagraphCxSpMiddle" style="margin-top: 0cm; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 18.0pt; mso-add-space: auto; text-align: justify; text-justify: inter-ideograph; text-indent: -18.0pt; line-height: 150%; mso-list: l0 level1 lfo1;"><!--[if !supportLists]-->2. <!--[endif]-->Among demographic factors, variables such as male and over 40 years of age were slightly more likely to be predisposed to the use of nutritional treatment. <p class="MsoListParagraphCxSpLast" style="margin-top: 0cm; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 18.0pt; mso-add-space: auto; text-align: justify; text-justify: inter-ideograph; text-indent: -18.0pt; line-height: 150%; mso-list: l0 level1 lfo1;"><!--[if !supportLists]-->3. <!--[endif]-->Pre-operative feeding support requires patients with oncological diagnosis, who stay in the ward for more than 4 days, and also those who have been taken on an emergency basis.